Mixing of natural and urban dust along the Wasatch Front of northern Utah, USA - Jeffrey S. Munroe; Gregory T. Carling; Kevin D. Perry; Diego P. Fernandez; Derek V. Mallia (Scientific Reports)
Abstract Understanding the composition and transport of mineral dust is essential for assessing its environmental and health impacts. We investigated the properties of mineral dust along the urbanized Wasatch Front in northern Utah (USA), comparing it with natural dust collected from upwind locations in the arid Great Basin. Using physical and geochemical analyses, we identified significant differences between urban and natural dust that are not attributable to the intervening landscapes. These differences arise from the mixing of natural dust with local anthropogenic materials, including sediments from the Great Salt Lake playa conditioned by over a century of urban activity. This urban-influenced dust is transported downwind, where it may contribute to elevated levels of cadmium, copper, and zinc in streams of downwind mountain watersheds. These findings underscore the far-reaching impact of urban dust on critical ecosystems and highlight the need for integrated management strategies to mitigate dust-related environmental consequences.